Crapemyrtle Pruning - Gary W. Knox; Edward F. Gilman; Teagan Young; Ryan Klein; Leynar Leyton Naranjo (EDIS)
Pruning is one of the most controversial aspects of maintaining crapemyrtle. Traditionally, many crapemyrtles were routinely topped, leaving large branch and stem stubs. This practice has been called "crape murder" because most people dislike the winter appearance and many professionals believe the practice impacts crapemyrtle health and structural integrity. UF/IFAS research has clarified the effects of various crapemyrtle pruning practices that resulted in the recommendations in this publication.